ANALISIS SISTEM INFORMASI PEMBELAJARAN LeADS UPN Veteran Jakarta MENGGUNAKAN METODE PIECES - Jessica Elfa Naomi (2023)
Current information system technology really helps everyone when carrying out each activity, one of which is becoming a learning medium in academic activities. E-learning is currently a medium that helps every learning activity. This learning information system is called a Learning Management System (LMS). This media makes it easier for students to access any learning information without knowing the time and place. This research aims to analyze the learning information system used at UPN Veteran Jakarta called LeADS (Learning Activities Through Digital System) which has been running so far. UPN Veteran Jakarta students and lecturers use LeADS to obtain lecture information that can be accessed anytime and anywhere. This research uses quantitative and qualitative descriptive to measure the condition of the LeADS learning information system so far. The population of this study are users of the LeADS LMS who are students and lecturers at UPN Veteran Jakarta. This research takes user assessments by taking a questionnaire where the statements used adapt the assessment to aspects of the PIECES method, such as Performance, Information, Economics, Control, Efficiency, and Security. The results obtained by user assessments from each aspect of the PIECES Framework have an average value, namely the Performance value is 3.94, the Information value is 3.43, Economics is 3.82, the Control value is 3.99, the Efficiency value is 4, 05, and the Security value is 3.86. So it can be seen that the LeADS learning information system when viewed from the PIECES analysis can be stated to be working well, and efficiently in its work, and has provided satisfaction for users of the LeADS learning information system itself.